P460 Preoperative nutrition supplementation may prevent one-year endoscopic recurrence in Crohn's disease patients. (30th January 2023) - Inniss, S; Simpson, K; Fragkos, K; Wood, C; Smith, A; Rahman, F
Abstract: Background: Despite improved postoperative management, endoscopic recurrence after surgery remains common in Crohn's disease (CD) patients [1] . It is widely accepted that patients receiving preoperative nutrition supplementation are less likely to experience postoperative complications [2] . However, little is known about the long-term effects of preoperative nutrition supplementation on surgery. In this study we aimed to assess the long-term effects of preoperative nutrition supplementation on endoscopic recurrence. Methods: Single centre retrospective data was collected between 2015 and 2021 on patients who had surgical resection with ileocolonic anastomosis. Follow up data was retrospectively collected at 12 months after surgery. Endoscopic recurrence was defined as a Rutgeerts score of 2 or more. Statistical analysis included demographics and inferential analyses. Missing data was attributed to the absence in clinic notes. Results: This study included 50 CD patients [50.0% male, median age of 31.0 (18.0-68.0), 81.8% non-smokers] who had ileocolonic anastomosis. Most patients had ileocolonic CD (76.0%, 38/50) and either stricturing (46.0%, 23/50) or penetrating (26.0%, 13/50) disease behaviour. Almost half (49.0%, 24/49) of CD patients received preoperative nutrition supplementation prior to surgery, with 61.9% on oral nutrition supplementation. No statistical difference was found between the demographics of patients receiving nutrition supplementation and patients without nutrition supplementation, p>0.05 (table 1). Endoscopic recurrence was observed in 43.5% (10/23) of patients at 12 months. 80.0% (8/10) of patients who experienced endoscopic recurrence did not receive preoperative nutrition supplementation (figure 1). Logistic regression indicated that patients receiving nutrition supplementation may be 84.4% less likely to experience endoscopic recurrence at 12 months compared to patients without nutrition supplementation (OR 0.16 (CI 0.023-1.056)(p=0.057)). The type of preoperative nutrition supplementation did not significantly impact endoscopic recurrence (p>0.05). Conclusion: Preoperative nutrition supplementation may reduce the risk of endoscopic recurrence one year after surgical resection. The use of preoperative nutrition is highly recommended for all CD patients undergoing surgery. More extensive research is needed to confirm study findings.